Stunting and academic trajectory in urban settings of Burkina Faso. - Rabi Joël Gansaonré; Lynne Moore; Jean-François Kobiané; Aly Sié; Slim Haddad (PLoS ONE)
Background Impaired growth in childhood can lead to poor cognitive development and low school performance. However, literature on the effects of stunting on school trajectory is very limited. The primary objective of this research was to estimate the age at which children start school according to levels of height-for-age z-score (stunting). A second objective was to estimate the gain in terms of age at school entry associated with an improvement in height-for-age z-score. A third objective was to explore the relationship between stunting, grade repetition, and school dropout. Methods We used longitudinal data from the Ouagadougou (Burkina Faso) Health and Demographic Surveillance System. Data from a 2010 health survey of children under 5 years of age were merged with subsequent longitudinal schooling data. The study included 767 children globally who participated in the health and education surveys. Education data allowed us to apprehend academic trajectory measured by age at school entry, repetition, and dropout. The health survey gathered anthropometric information that was used to measure stunting. The adjusted age at school entry was estimated using a Poisson model. The gain represents the difference in adjusted age at school entry for different values of height-for-age. The relationship between stunting and grade repetition and dropout was studied using a discrete-time survival model. Results Results showed that children entered school on average at 5.7 years old, and the incidence of grade repetition and dropout was 17.7 and 6.6 per 100 persons-years, respectively. The adjusted age at school entry of severely stunted children was 6.2 years [95% confidence intervals (CI): 6.1; 6.3] compared to 5.1 years [95% CI: 5.0; 5.3] for children who had normal growth. The difference (gain) in adjusted age at school entry between severely and non-stunted children was thus 1.06 [95% CI: 0.87; 1.25] years. If a child's growth changed from severe stunting to normal growth, their risk of repeating a grade decreased by 5.0 [95% CI: 0.0; 9.0] per 100 persons-years. We did not observe a relationship between height-for-age and dropout. Conclusion The results show that schooling is affected in several ways for children who are stunted. The age at school entry of stunted children is more likely to be delayed. Also, being stunted is associated with higher incidence of grade repetition. However, the relationship between stunting and dropout was inconclusive.